PROXIMATE AND PHYTOCHEMICAL PARAMETERS OF LEAVES OF MEDICINAL PLANT Murraya koenigii - RICHA DODIA* and SUSMITA SAHOO, (The Journal of Research ANGRAU, 2022)
The purpose of this research work is to evaluate the proximate and phytochemical componentsof Murraya koenigii leaves from Vadodara and Anand cities of Gujarat for their efficacy beforeincorporation into the formulation. Murraya koenigii leaves were collected from June-July in the year2021. Murraya koenigii leaves have been used to control diabetes. The leaves were evaluated bydetermining physicochemical parameters including total ash, acid insoluble ash, water-soluble ash,and moisture content. Phytochemical parameters included total phenolic content, total flavonoidcontent, and total tannin content in terms of gallic acid, quercetin, rutin, and tannic acid equivalents,respectively. The quantitative proximate investigation of Murraya koenigii plant leaves showed leavesof Anand city have a total ash content 15.66±0.32% w/w, acid-insoluble ash 0.59±0.01% w/w, moisturecontent 1.12±0.03% w/w respectively compared to Vadodara city total ash content 12.29±0.08% w/w,acid-insoluble ash 0.20±0.02 %w/w, moisture content 1.31±0.12 %w/w, respectively. However, Anandcity leaves have a lower water-soluble capacity of 0.91±0.06% w/w compared to Vadodara city at7.34±0.40% w/w. In this study, leaves of Vadodara city showed a high quantity of total phenolics, totalflavonoids, and total tannin phytoconstituents 101.50±0.92 mg of GAE/g, 163.83±0.87 mg of RT /g,128.16±0.76 mg of TAE/g compared to Anand city 61.58±0.62 mg of GAE/g,126.66±1.04 mg of RT /g, 64.16±1.44 mg of TAE/gconcerning gallic acid, rutin, and tannic acid. However, the leaves ofAnand city showed a high quantity of total flavonoids 101.16±1.28 mg of QE/g compared to Vadodaracity at 59.0±0.09 mg of QE/g concerning quercetin